1990
DOI: 10.1111/j.1476-5381.1990.tb14158.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative inotropic effects of disopyramide on guinea‐pig papillary muscles

Abstract: The inhibitory effects of disopyramide on electromechanical responses were investigated in guinea‐pig papillary muscles driven by electrical stimuli. Disopyramide up to 10−5 m did not cause a negative inotropic effect, while the maximum upstroke velocity of the action potential (dV/dtmax) was significantly decreased. At higher concentrations, this drug dose‐dependently inhibited the contraction, and dV/dtmax was further decreased. This inhibition of contraction was accompanied by a depression of the slow actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…2A, 3B, C) and showed negative chronotropic and inotropic effects ( fig. 4), which is similar to the effects of Ca 2+ channel antagonists such as verapamil [3,4,18,19]. Moreover, HNS-32 at higher concentrations inhibited the initial peak of the inactivating inward current on depolarization ( fig.…”
Section: Discussionsupporting
confidence: 60%
“…2A, 3B, C) and showed negative chronotropic and inotropic effects ( fig. 4), which is similar to the effects of Ca 2+ channel antagonists such as verapamil [3,4,18,19]. Moreover, HNS-32 at higher concentrations inhibited the initial peak of the inactivating inward current on depolarization ( fig.…”
Section: Discussionsupporting
confidence: 60%
“…The myocardial contractile force under elevated extracellular K + concentration, used in the present study, was shown to be highly dependent on Ca 2+ channel function. 9,10) The present observation that the negative inotropic effect of class I antiarrhythmic drugs observed under normal conditions was mostly preserved under elevated extracellular K + conditions implies the involvement of Ca 2+ channel blockade. The negative effects of all drugs tended to converge on a single concentration-response curve when the concentration of each drug was expressed as a ratio against its IC 50 value for Ca 2+ channel blockade (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…The effects of class I antiarrhythmic drugs were also examined under elevated extracellular K + concentration, under which the function of Na + channels is markedly reduced while the dependence of myocardial contraction on the Ltype Ca 2+ channel is maintained 9,10) ; this was confirmed by the observation that the contractile force was highly sensitive to nifedipine but not to tetrodotoxin. The contractile force under elevated extracellular K + concentration was decreased to 10.7 ± 3.9% (n = 5) with 1 µM nifedipine, but to 89.1 ± 3.0% (n = 5) with 10 µM tetrodotoxin.…”
Section: Resultsmentioning
confidence: 98%
“…Although disopyramide is a weak calcium channel antagonist, its principal native inotropic effect appears to be mediated by sodium-calcium exchange. 69 Pollick and associates 70 administered intravenous disopyramide to 43 patients with HOCM. The LVOT gradient was abolished or reduced; the effect was greater than that seen previously for either propranolol or verapamil.…”
Section: Disopyramidementioning
confidence: 99%